The Effects of Building a Local Brand by Municipial Level: Case Study - Urszula ZIEMIANCZYK; Piotr NOSALSKI (Communications of International Proceedings, 2021)
Territorial marketing is playing an increasingly important role in managing places. With the changing paradigm of public administration and the emergence of concepts like New Public Management (NPM), local government administrators need to implement performance monitoring tools to measure the effectiveness and efficiency of the strategies used. It is widely recognised that, like a corporate brand, a place brand can act as an umbrella brand to support the promotion and branding of various products, services and places associated with a given place (Anholt, 2004; Iversen & Hem, 2008). The aim of the research is to present the implemented technologies - and their verifiable selected effects - used in a chosen local government unit. The purpose of the local government investment was to build a consistent message and image while building a local brand. The solutions applied in the unit - commune of Liszki in Poland - are a perfect example of how technology can support to build a local brand and facilitate communication in local commune, supporting the work of officials and at the same time making the lives of residents and other groups easier. It is an outstanding example of activities in the win-win model, where all parties involved benefit. It is a prime example of how every municipality can practice effective, unobtrusive marketing, using simple but coherent and integrated solutions.
Keywords: Marketing; Public Managers; Local Brand; Commune; Municipial Level